A comparative evaluation of canal transportation, centering ability, and volumetric increase in the curved canals using thermally treated three nickel-titanium rotary files: A cone-beam computed tomography study - Meenu G Singla; Hemanshi Kumar; Neha Singh (Wolters Kluwer Medknow Publications, 2021)
Aims: The aim of this study was to evaluate and compare canal transportation (CT), centering ability (CA), and volumetric changes in the curved canals prepared using Hyflex Electrical Discharge Machining (HEDM), ProTaper Gold (PG), and NeoEndo Flex rotary file systems through cone-beam computed tomography (CBCT). Materials and Method: Sixty mesiobuccal canals of maxillary molars were selected. Pre- and postinstrumentation CBCT scans were taken in the same position. CT and CA were calculated at 1 mm, 4 mm, and 7 mm from the apex; change in volume for the whole canal was measured and analyzed statistically. Results: The results showed that mean CT of HEDM and NeoEndo was less than PG at all levels, with significant differences at 4 mm and 7 mm. Regarding CA, no significant differences were found among the file systems. PG showed maximum volumetric increase with no statistically significant differences between the groups. Conclusion: All the experimental file systems respected the canal anatomy, although in the middle third, PG showed significantly more CT than HEDM and NeoEndo, whereas in the coronal third, PG showed significantly greater CT than NeoEndo. Regarding CA, no significant differences were found among the file systems. PG showed maximum volume of dentin removal.